Supplier selection framework for strategic government procurement - Chai, Khin Chung (2005)
This research project is a study on supplier selection decision-making framework on strategic government procurement. Current practices do not allow balanced tradeoffs to reach optimal procurement decisions consistently. The main drawback of the current system can be traced to the practice of the lowest acceptable offer principle which is not capable of establishing any scientific relationship between the price and quality criteria and therefore, unsure of identifying the best bid and maintain decision consistency. Due to absence of scientific structured supplier selection method in the present system, supplier selection decision-making process is heavily skewed to decision-makers’ intuition and ad hocism; no clear audit trail exists and, therefore lacks system transparency. The main objective of this study is to propose a framework that is capable of overcoming the major systemic weaknesses, namely, lacking of proper guidelines and clear framework that can be used to make balanced and consistent supplier selection decisions for complex system procurement. The study uses Royal Malaysia Police as an example and the procurement of a complex telecommunications system as a case study. Focus interview was used to identify buyers’ strategic orientation, main and sub supplier selection decision criteria. Via focus interview, RMP procurement practitioners also suggested that closer working relation between the financial and technical evaluation committees could be more effective in identifying the best bid. Literature review suggested the total cost of ownership procurement principle is widely used among the more progressive companies globally and Analytic Hierarchy Process (AHP) emerged as the most suitable decision-making technique for supplier selection. Based on the above findings, a generic framework was established. The proposed framework was tested successfully in an actual tender evaluation of complex telecommunications system procurement. Being scientific, explicit, transparent and objective, it was capable of addressing the current systemic weaknesses satisfactorily. The framework was able to bridge the policy/implementation gap of the Treasury Instruction and is capable of realising the desire of practicing total cost of ownership (TCO) principle in the Malaysian government procurement function. Testimonies on the relevancy and applicability the AHP based supplier selection decision-making framework by the Chairman of the technical evaluation committee and the Chairman of the Home Ministry Tender Board, confirmed the success of the framework under test and also this project as a whole. The proposed framework when modified is suitable for any kind of purchase in other government departments or agencies.